1975
DOI: 10.1111/j.1365-2125.1975.tb01572.x
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of oral (‐)‐tryptophan in human subjects.

Abstract: 1 The psychotropic effects of a single oral dose of (‐)‐tryptophan (5 g) in human volunteers were investigated using a series of physiological and psychological tests. 2 Self‐ratings of mood showed increase in drowsiness but no euphoria was detected. 3 Severe initial nausea occurred and headache increased; other bodily symptoms were unaffected. 4 Trptophan caused increased activity in the slow wavebands of the EEG but did not alter the other physiological measures. 5 The levels of total and free tryptophan in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 38 publications
1
29
1
Order By: Relevance
“…Finally, regarding the safety of L-Trp, sleepiness, headache, nausea, postural discomfort, and paleness and diarrhea were observed in the subjects administered L-Trp at doses more than 4 g accompanying the increases in Trp levels in serum. Similar adverse reactions to L-Trp have been also reported (Greenwood et al, 1975;Yuwiler et al, 1981;Lieberman et al, 1984). It was concluded that a single administration of L-Trp was tolerated up to 4 g. In summary, the results of this study have demonstrated that IS was highly bound to serum protein and the major renal elimination route for IS was renal tubular secretion in humans.…”
Section: Discussionsupporting
confidence: 66%
“…Finally, regarding the safety of L-Trp, sleepiness, headache, nausea, postural discomfort, and paleness and diarrhea were observed in the subjects administered L-Trp at doses more than 4 g accompanying the increases in Trp levels in serum. Similar adverse reactions to L-Trp have been also reported (Greenwood et al, 1975;Yuwiler et al, 1981;Lieberman et al, 1984). It was concluded that a single administration of L-Trp was tolerated up to 4 g. In summary, the results of this study have demonstrated that IS was highly bound to serum protein and the major renal elimination route for IS was renal tubular secretion in humans.…”
Section: Discussionsupporting
confidence: 66%
“…Of course, sleep parameters were determined in a group of patients not complaining of insomnia. Unlike other studies [14,15,19] we did not observe an increase in drowsiness.…”
Section: Discussioncontrasting
confidence: 55%
“…Previously, Greenwood, Lader, Kantameneni, & Curzon (1975) reported an increase in the voltage of the 4.0-7.5 Hz and 2.4-4.0 Hz frequency bands after tryptophan loading. While these authors did not report any change in the alpha band, they recorded the EEG during performance of a reaction time task, an experimental situation which may have precluded effects on alpha activity.…”
Section: Discussionmentioning
confidence: 99%